Giant Tug Lesion of the Soleus - Dima Al Jahed; Filip Vanhoenacker (Journal of the Belgian Society of Radiology, 2021)
Teaching point: A giant soleus tug lesion is a benign pseudo-tumoral excrescence at the attachment of the soleus muscle at the posterior upper third of the tibia.